Copper Hexacyanoferrate Formation on the Modified Silica Surface with DAB-Am-16 Dendrimer - do Carmo, Devaney R. [UNESP] (2011)
The third generation (G-3) polypropylenimine hexadecaamine dendrimer (DAB-Am-16) was grafted onto the silica gel surface. The modified silica interacts easily with Cu(2+) and then with potassium ferrocyanide to form copper hexacyanoferrate. The modified silica was characterized by the following techniques: Nuclear Magnetic Resonance (NMR), FTIR spectroscopy, Energy Dispersive X-ray (EDX) and Cyclic Voltammetry. The modified silica containing copper hexacyanoferrate (CuHCFSD) was tested for a voltammetric determination of nitrite using a modified graphite paste electrode.